Thermo-physical, tribological and machining characteristics of Hastelloy C276 under sustainable cooling/lubrication conditions. (August 2022) - Ross, Nimel Sworna; Srinivasan, N.; Amutha, P.; Gupta, Munish Kumar; Korkmaz, Mehmet Erdi
Abstract: Chemical reactivity and poor heat conductivity make nickel (Ni) and its alloys difficult to process. The aerospace industry's expectations for high-quality surfaces are one of the biggest hurdles in machining nickel components. Recent studies have found some flaws in mist lubrication techniques when utilised under high-speed cutting circumstances, thus nanoparticles with higher thermal conductivity than the base fluid is now being used in minimum quantity lubrication (MQL) systems. Nanocarbon dots (CDs) blended with bio lubricant is an effective coolant to enhance the heat transfer capability by decreasing friction. The inclusion of the right nanoparticle ratio to the base liquid is one of the most important challenges that arise when machining. This research focuses on a deeper exploration of Hastelloy C276's tribological behaviour and machinability under various cutting approaches (Dry, MQL Cryo CO2 and N-MQL). Milling trials were carried out with various speed-feed pairings and cutting conditions. Outcomes show that 0.8 wt% CDs with soybean oil reduces the surface roughness by 56–69 %, 15–24 %, and 15–26 % over dry, MQl and cryo CO2 environments. According to elemental study of cutting inserts, adhesion is the primary wear mechanism in all cutting mediums. Finally, the chillness produced by cryo CO2 has a positive effect compared to the N-MQL strategy by producing fine grains.